China's energy economy: Technical change, factor demand and interfactor/interfuel substitution - Ma, H.; Oxley, Leslie; Gibson, J.; Kim, B. (Elsevier, 2008)
With its rapid economic growth, China's primary energy consumption has exceeded domestic energy production since 1994, leading to a substantial expansion in energy imports, particularly of oil. China's energy demand has an increasingly significant impact on global energy markets. In this paper Allen partial elasticities of factor and energy substitution, and price elasticities of energy demand, are calculated for China using a two-stage translog cost function approach. The results suggest that energy is substitutable with both capital and labor. Coal is significantly substitutable with electricity and complementary with diesel while gasoline and electricity are substitutable with diesel. China's energy intensity is increasing during the study period (1995-2004) and the major driver appears to be due to the increased use of energy-intensive technology. © 2008 Elsevier B.V. All rights reserved.